Sussing merger trees: the impact of halo merger trees on galaxy properties in a semi-analytic model - Lee, Jaehyun; Yi, Sukyoung K.; Elahi, Pascal J.; Thomas, Peter A.; Pearce, Frazer R.; Behroozi, Peter; Han, Jiaxin; Helly, John; Jung, Intae; Knebe, Alexander; Mao, Yao-Yuan; Onions, Julian; et al. (Oxford University Press, 2014)
A halo merger tree forms the essential backbone of a semi-analytic model for galaxy formation and evolution. Recent studies have pointed out that extracting merger trees from numerical simulations of structure formation is non-trivial; different tree building algorithms can give differing merger histories. These differences should be carefully understood before merger trees are used as input for models of galaxy formation. We investigate the impact of different halo merger trees on a semi-analytic model. We find that the z = 0 galaxy properties in our model show differences between trees when using a common parameter set. The star formation history of the universe and the properties of satellite galaxies can show marked differences between trees with different construction methods. Independently calibrating the semi-analytic model for each tree can reduce the discrepancies between the z = 0 global galaxy properties, at the cost of increasing the differences in the evolutionary histories of galaxies. Furthermore, the underlying physics implied can vary, resulting in key quantities such as the supernova feedback efficiency differing by factors of 2. Such a change alters the regimes where star formation is primarily suppressed by supernovae. Therefore, halo merger trees extracted from a common halo catalogue using different, but reliable, algorithms can result in a difference in the semi-analytic model. Given the uncertainties in galaxy formation physics, however, these differences may not necessarily be viewed as significant.